2013
DOI: 10.3109/13561820.2013.783558
|View full text |Cite
|
Sign up to set email alerts
|

Newly qualified doctors’ perceptions of informal learning from nurses: implications for interprofessional education and practice

Abstract: Newly qualified doctors spend much of their time with nurses, but little research has considered informal learning during that formative contact. This article reports findings from a multiple case study that explored what newly qualified doctors felt they learned from nurses in the workplace. Analysis of interviews conducted with UK doctors in their first year of practice identified four overarching themes: attitudes towards working with nurses, learning about roles, professional hierarchies and learning skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…34 The case study observations and considerations of newly qualified doctors and experienced nurses portrayed a complex structure where awareness of nurses' expertise was evident, but superseded by the culture of continuing medical dominance. 36 A recent study by Barrow et al 2 used an Activity Theory framework, similar to that used here, to consider conceptual differences between doctors and nurses in hospitals. The authors suggested that co-configured, joined-up work was evident in their study, and the traditional hierarchy was overruled at times by attention to competence.…”
Section: Discussionmentioning
confidence: 99%
“…34 The case study observations and considerations of newly qualified doctors and experienced nurses portrayed a complex structure where awareness of nurses' expertise was evident, but superseded by the culture of continuing medical dominance. 36 A recent study by Barrow et al 2 used an Activity Theory framework, similar to that used here, to consider conceptual differences between doctors and nurses in hospitals. The authors suggested that co-configured, joined-up work was evident in their study, and the traditional hierarchy was overruled at times by attention to competence.…”
Section: Discussionmentioning
confidence: 99%
“…Few IPE programs included any form of formal academic accreditation. Further, most IPE programs were delivered as elective learning experiences to participants, where some of the school accepted the credit hours but some were not (Burford et al, 2013;Joseph et al, 2012;Zanoti & Canova, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Programs were more commonly delivered to students in the final year as a classroom or sometimes as a practice-based activity. Also, the synthesis of the reviews indicated that while the duration of IPE program varied, ranging from 1-to-2 days' sessions to programs delivered over a period of the year; most programs lasted between 1-3 months (Burford et al, 2013). …”
Section: Other Professionals Involved With Nursingmentioning
confidence: 99%
See 2 more Smart Citations